2014
DOI: 10.3390/molecules190913188
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of a Series of 2-Amino-Naphthoquinones against Human Cancer Cells

Abstract: ) than values shown by tumour cell lines. The mechanism of cell growth inhibition and structure-activity relationships remains as a target for future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
24
0
2
Order By: Relevance
“…The compounds used in this study ( Figure 1) are novel, synthetically-derived polycyclic aromatic hydrocarbons, belonging to the aminonaphthoquinone class of compounds (coded Rau 008, Rau 010, Rau 015 and Rau 018). Aminonaphthoquinones have shown potential as anti-cancer agents (28,29). In particular, the cytotoxicity of Rau 010 and Rau 018 was assayed against cervical carcinoma (HeLa) and T-cell leukaemia (Jurkat) cells and it was found that these aminonaphthoquinones showed significant anti-proliferative activity against both cell lines (29).…”
mentioning
confidence: 99%
“…The compounds used in this study ( Figure 1) are novel, synthetically-derived polycyclic aromatic hydrocarbons, belonging to the aminonaphthoquinone class of compounds (coded Rau 008, Rau 010, Rau 015 and Rau 018). Aminonaphthoquinones have shown potential as anti-cancer agents (28,29). In particular, the cytotoxicity of Rau 010 and Rau 018 was assayed against cervical carcinoma (HeLa) and T-cell leukaemia (Jurkat) cells and it was found that these aminonaphthoquinones showed significant anti-proliferative activity against both cell lines (29).…”
mentioning
confidence: 99%
“…Cytotoxic activity of 4'-leucinoavarone was recently studied in more details [44,45]. (peripheral blood mononuclear cells) [46]. For this type of compounds, glycine, alanine and phenylalanine derivatives showed a better activity than β-alanine and proline ones.…”
Section: Fig 3 Tautomeric Forms Of Avarone and Tert-butylquinone Dementioning
confidence: 98%
“…The mechanism of fighting against microorganisms using amino-naphthoquinones has been elucidated in detail in a previous publication [8][9][10]. In brief, the amino-naphthoquinones inhibits growth of microorganisms by using an electrochemical mode of action to penetrate and disrupt their essential structures.…”
Section: Investigation Of the Treated Oxidation Cotton Fabric With Namentioning
confidence: 99%